CRTAC1 (Cartilage acidic protein 1) inhibits cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) process in bladder cancer by downregulating Yin Yang 1 (YY1) to inactivate the TGF-β pathway - Jianghua Yang (Taylor & Francis Group, 2021)
Cartilage acidic protein 1 (CRTAC1) is predicted to be aberrantly expressed in bladder cancer based on bioinformatics analysis. However, its functions and molecular mechanism in bladder cancer remain elusive. This study aimed to explore the role of CRTAC1 in bladder cancer. The mRNA and protein levels of CRTAC1 and Yin Yang 1 (YY1) were detected by reverse transcription quantitative polymerase chain reaction and western blotting. We found that CRTAC1 was downregulated in bladder cancer tissues and cells. Cell Counting Kit-8 assays, colony formation assays, wound healing assays and Transwell assays and western blotting revealed that CRTAC1 overexpression inhibited cell viability, proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) process in bladder cancer, while CRTAC1 knockdown exerted opposite effects on these malignant behaviors. Mechanistically, CRTAC1 targeted YY1 in bladder cancer cells. YY1 was upregulated in bladder cancer tissues and cells. CRTAC1 negatively modulated the mRNA and protein expression of YY1 in bladder cancer cells. Co-localization of CRTAC1 and YY1 expression was assessed using immunofluorescence staining and Co-Immunoprecipitation assays. The interaction between CRTAC1 and YY1 was explored by Chromatin immunoprecipitation and luciferase reporter assays. Moreover, CRTAC1 inactivated the TGF-β pathway by downregulating YY1 expression. Protein levels of factors associated with the TGF-β pathway were examined by western blotting. Rescue assays indicated that CRTAC1 inhibited malignant behaviors of bladder cancer cells by targeting YY1. Overall, CRTAC1 inhibited malignant phenotypes of bladder cancer cells by targeting YY1 to inactivate the TGF-β pathway.